Kagurabachi. 03, Knight of darkness - Hokazono, Takeru (Shonen Jump manga., 2025)
"Chihiro Rokuhira's father, Kunishige, is the most famous swordsmith in the land. Thanks to his six enchanted blades, the war that has been gripping the nation ends, and peaceful days follow. After thewar, he retrieves all six blades and hides them in the cellar of his workshop-but sorcerers raid his home and leave Kunishige dead in front of Chihiro. Many years later, Chihiro wields Kunishige's seventh and final enchanted blade on a mission to retrieve the stolen swords! The strongest enchanted blade, known as the Shinuchi, is up for sale at a black market. Chihiro's determined to steal the Shinuchi back, but standing in his way are skilled sorcerers devoted to safeguarding the auction. Can Chihiro slash his way through and reclaim the fabled katana?"--